Design a New Sliding Mode Adaptive Hybrid Fuzzy Controller. - Sulaiman, Nasri (2011)
One of the most important challenges in nonlinear, multi-input multi-output (MIMO) and time variant systems (e.g., robot manipulator) is designing a controller with acceptable performance. This paper focuses on design a new sliding mode on-line tunable gain hybrid fuzzy control (SMHFLC) applied in the robot manipulator. The PD fuzzy controller is designed as 49 rules Mamdani's error based which the integral error controller is added to the fuzzy controller to get the better performance. One of the most important robust non linear methodologies is sliding mode method. On-line tuning is used in systems with various dynamic parameters, structure and unstructured uncertainties and need to be training on line. Therefore combined adaptive method and hybrid PD fuzzy controllers can solve the uncertainty challenge in nonlinear systems.